1997
DOI: 10.1109/20.560112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glass removal on the magnetic behavior of FeSiB glass-covered wires

Abstract: Amorphous magnetic glass-covered wires are of interest for basic research and potential applications. Their specific magnetic behavior originates in their very small diameters and in the high internal stresses induced during preparation. emoval of the glass cover leads to significant changes in their magnet~c ~r o p e r t~e s and behavior, thus improving their suitability for sensing applications. A thorough study of the changes produced by the glass removal implies the consideration of the changes produced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…microwires with larger ratios between glass coating thickness and metallic core radius [6]. In the case of sample A, this ratio is 1.97, while in the case of sample B it is 1.33.…”
Section: Methodsmentioning
confidence: 91%
“…microwires with larger ratios between glass coating thickness and metallic core radius [6]. In the case of sample A, this ratio is 1.97, while in the case of sample B it is 1.33.…”
Section: Methodsmentioning
confidence: 91%
“…The large internal stresses induced by both rapid solidification of metal and the difference between the thermal expansion coefficients of metal and glass (Chiriac et al, 1995) give rise to quite large values of the switching field, as shown in Figures 20 and 21. The direct relation between the value of the switching field and the glass to metal ratio is well known (Chiriac et al, 1997). In case of the (Co 0.94 Fe 0.06 ) 72.5 Si 12.5 B 15 samples magnetostriction is much smaller leading to smaller values of the switching field.…”
Section: Rapidly Solidified Amorphous Nanowiresmentioning
confidence: 96%
“…In these works, magnetic properties of Fe77 sSij sBls AGCMW are analyzed starting from the magnetoelastic coupling between their high positive magnetostriction (1 = 35 x and internal stresses induced during preparation. This coupling leads to a strong magnetoelastic anisotropy which mainly determines their magnetic behavior [4]. The magnetic behavior of Feq7 sSi7,5B15 AGCMW was explained from the point of view of the magnetoelastic anisotropy originating in the coupling between magnetostriction and the diagonal components of the internal stress tensor.…”
Section: Introdljctionmentioning
confidence: 99%
“…The aim of this paper is to study the helical anisotropy in Fe77 5Si7.5Bl AGCMW, and the way it affects the known easy axes distribution established for these wires 121, [3], and also to study the torque sensitivity of the magnetic behavior of glass-covered wires and of wires obtained after glass removal"…”
Section: Introdljctionmentioning
confidence: 99%
See 1 more Smart Citation